The Influence of Village Fund Use on the Welfare of the Bintuas Village Community, Mandailing Natal Regency: With Transparency as a Moderating Variable - Asmiannur, Asmiannur; Tambunan, Khairina; Syafina, Laylan (Pusat P2M Politeknik Negeri Batam, 2026)
This study aims to examine and determine the effect of the use of Village Funds on community welfare and to examine the role of transparency as a moderating variable in the relationship. This study uses a Quantitative research type with an Associative Causal Approach. The data source comes from Primary Data with Data Collection Techniques using questionnaires distributed via Google Forms. The population of this study is the community of Bintuas Village, Natal District, Mandailing Natal Regency, totaling 1,136 people, the sampling technique used was the Purposive sampling method using the Slovin formula with an error rate of 10% so that a sample of 91.90 was obtained which was rounded up to 92 respondents. Data analysis used to process the data of this study is Using Moderated Regression Analysis (MRA) with the help of the SPSS 26 program. The results of this study indicate that the use of village funds has a positive effect on community welfare. Transparency is proven to significantly moderate the relationship. An interesting finding is the negative direction of moderation, which indicates that a high level of transparency actually weakens the strength of the positive influence of the use of village funds on welfare. This is interpreted as a trade-off between the demands of formal accountability of high transparency, weakening the agility that has a direct impact on village spending.